THE ROLE OF GOVERNMENT TOURISM OFFICE IN THE DEVELOPMENT OF TOURISM OBJECTS OF CIPOGAS LAKE ROKAN HULU - Dinda Pratiwi; Siti Sofro Sidiq (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This research was conducted in Cipogas Lake, Rokan Hulu, Riau- Indonesia. The Cipogas lake Rokan Hulu Tourism Object is one of the tourist attractions that is used as a superior product in Rokan Hulu Regency. As one of the leading tourism, Cipogas Lake development planning will be carried out by taking into account the role of the Tourism Office in developing the Cipogas Lake Rokan Hulu Tourism Object. This study aims to determine the role of the Tourism Office in the Development of Cipogas Lake Rokan Hulu Tourism Object. This study uses a qualitative descriptive method to process data obtained in the field through interviews, observation and documentation. All information is collected and studied so that it becomes a complete unit (Sugiono. 2000). Meanwhile, for the sample in the study, there were 6 key information persons. Based on the results of research that has been carried out, the role of the Tourism Office in the Development of Cipogas Lake Tourism Objects is as a Motivator, Facilitator, and Dynamator to develop Cipogas Lake Tourism Objects and increase Tourist Visits.Keywords: The Role of the Tourism Office, Development, Tourist Attraction